Efeito da prática de ballet clássico no controle postural de escolares - Pinto, Kélen Munhos (2019)
This dissertation aimed to compare the effect of classical ballet practice time on dynamic postural control and lower limb functionality of ballerinas with more than one year of practice and ballerinas with two months of classical ballet practice; and also compare non-practicing classical ballet students with practicing students during two months of practice. Two articles were produced to answer the questions of this dissertation. Seven girls in each group participated in the studies. The assessments consisted of lower limb dominance definition, warm-up, anamnesis, regular physical activity questionnaire - PAC-C, functional assessment and dynamic postural control assessments. For this, some questionnaires were used for sample characterization, kinetic analysis system and functionality instrument. As a result the articles showed that experienced school-age dancers who have been around for 10 years appear to have better dynamic postural control in performing jumps compared to inexperienced dancers of the same age group. The inexperienced dancers presented higher performance in lower limb functionality in the posteromedial direction and similar behavior in the anteroposterior and posterolateral directions compared to the experienced dancers. Preliminary results have also shown that short-term classical ballet practice has benefits for lower limb functionality and dynamic postural control in schoolchildren.